Estimation of durability of carrier shafts in eccentric mechanisms - Arinova, Dinara; Uspensky, Borys; Avramov, Konstantin; Povetkin, Vitaly (Eastern-European Journal of Enterprise Technologies, 2019)
This paper has suggested a procedure to analyze durability of supporting shafts in eccentric mechanisms based on finite-element modeling. When conducting the analysis, the steady movement of the mechanism is investigated. The analysis of durability is based on the model of additive accumulation of damage. The shaft stress assessment is carried out based on the finite-element modeling of the mechanism that operates under a steady mode at working frequencies that are closest to the critical ones. Following the detection of stress concentrators and the most stressed shaft regions, an analysis of the characteristic cycle of loading is performed. After reducing a loading cycle to a series of symmetric cycles, the shaft damage assessment at each cycle is performed and its resource is estimated. Based on the proposed method, we have analyzed durability of a carrier shaft in the centrifugal-gyratory ore mill of link type. A simplified estimated model has been built based on the mechanical model in order to improve efficiency and performance of the finite-element calculation. The model of ore movement in grinding chambers under a steady motion mode has been proposed. We have built the Campbell’s diagrams for oscillations of the system and have established that the mill’s mechanism is not part of the resonance at the working frequency of excitation. The region of mechanical stresses concentration and the region of maximal mechanical stresses in the mill shaft have been identified. The shaft operating conditions have been analyzed and a value for the shaft material’s endurance limit in the zone of greatest stresses has been calculated. We have built a characteristic cycle of the mill shaft loading under a steady mode of operation, which consists of 16 sections. Each section has been reduced to a symmetric cycle, which has made it possible to calculate shaft damage at each section of the cycle and over the entire load cycle in general. Application of the additive damage accumulation procedure has made it possible to estimate the resource of a mill shaft. The proposed methodology for estimating durability of the carrier shaft could be used to analyze the resource of various mining and processing mechanisms, light industry equipment, and vibration generators